Pengaruh Digital advertising dan Keunikan Produk terhadap Keputusan Pembelian Produk Fashion Lokal Locke Pecke pada Pengguna Facebook di Kota Bima - Ismunandar Ismunandar; Sri Asmiatiningsih; Muhammad Lutfi; Nur Khusnul Hamidah (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2026)
This study aims to examine the effect of digital advertising and product uniqueness on the purchase decision of Locke Pecke local fashion products among Facebook users in Bima City. This research employed a quantitative approach with a causal associative research design. The population of this study consisted of Facebook users in Bima City who had known, seen, interacted with, or purchased Locke Pecke products. The sample consisted of 100 respondents selected using a purposive sampling technique. Data were collected through questionnaires and analyzed using validity tests, reliability tests, multiple linear regression analysis, correlation coefficient, coefficient of determination, t-test, and F-test with the assistance of SPSS. The results showed that digital advertising had a positive and significant effect on purchase decisions, with a significance value of 0.007. Product uniqueness also had a positive and significant effect on purchase decisions, with a significance value of 0.005. Simultaneously, digital advertising and product uniqueness had a positive and significant effect on purchase decisions, with a significance value of 0.002. The correlation coefficient value of 0.603 indicates a moderately strong relationship, while the R Square value of 0.364 indicates that digital advertising and product uniqueness explain 36.4% of the variation in purchase decisions, while the remaining percentage is influenced by other factors not examined in this study.